2021
DOI: 10.3390/bs11060079
|View full text |Cite
|
Sign up to set email alerts
|

Motor Vehicle Collisions during Adolescence: The Role of Alexithymic Traits and Defense Strategies

Abstract: International literature has shown that adolescents represent the population most at risk of fatal and nonfatal motor vehicle collisions (MVCs). Adolescents’ alexithymic traits and significant use of immature defense strategies have been seen to play a key role. This study aimed to investigate the possible mediation role played by defense strategies use in the relationship between alexithymia and MVCs. Our sample consisted of 297 adolescents divided into four subgroups, based on the number of visits to the eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 112 publications
(156 reference statements)
3
7
0
Order By: Relevance
“…On the other hand, emerging adults who experienced severe distress due to the COVID-19 pandemic showed the greatest difficulties in describing feelings and the highest scores of Internet and Instagram addiction. These findings are in line with our hypotheses and with numerous studies showing alexithymia to be among the individual vulnerabilities underlying a higher psychopathological risk [ 110 , 139 , 140 , 141 ], especially resulting from stressful life experiences [ 142 , 143 ]. An emerging adult with difficulties in regulating and identifying his/her emotions may be at higher risk in coping with stressful events, due to a deficit in symbolic thinking [ 144 ] and in processing and regulating his/her feelings-related responses [ 145 ].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, emerging adults who experienced severe distress due to the COVID-19 pandemic showed the greatest difficulties in describing feelings and the highest scores of Internet and Instagram addiction. These findings are in line with our hypotheses and with numerous studies showing alexithymia to be among the individual vulnerabilities underlying a higher psychopathological risk [ 110 , 139 , 140 , 141 ], especially resulting from stressful life experiences [ 142 , 143 ]. An emerging adult with difficulties in regulating and identifying his/her emotions may be at higher risk in coping with stressful events, due to a deficit in symbolic thinking [ 144 ] and in processing and regulating his/her feelings-related responses [ 145 ].…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the specific role played by late adolescents' alexithymia on the psychological impact of COVID-19, our results have confirmed that higher levels of alexithymia are predictive of late adolescents' emotional-behavioral difficulties [96][97][98]. This could be due to the difficulties in regulating and identifying own and others' feelings [58][59][60], which would expose the late adolescent to greater vulnerability in coping with stressful situations [53][54][55][56].…”
Section: Main Findingssupporting
confidence: 57%
“…Especially when adolescents visit the emergency room several times, we could consider this behavior as an unconscious attempt to obtain psychological help [ 29 ]. Coherently with recent literature aimed at investigating variables related to the high rates of traffic collisions observed in adolescents [ 11 , 23 , 25 ], we emphasize the importance of considering the dynamic interplay between factors of different natures, environmental, individual, and relational, placing particular emphasis on the role played by the family and the adolescent’s psychological functioning. Other studies have underlined the importance of family when studying risky behaviors in general and related to driving in adolescence [ 23 , 25 ].…”
Section: Introductionmentioning
confidence: 97%
“…Coherently with recent literature aimed at investigating variables related to the high rates of traffic collisions observed in adolescents [ 11 , 23 , 25 ], we emphasize the importance of considering the dynamic interplay between factors of different natures, environmental, individual, and relational, placing particular emphasis on the role played by the family and the adolescent’s psychological functioning. Other studies have underlined the importance of family when studying risky behaviors in general and related to driving in adolescence [ 23 , 25 ]. Not only does adequate family communication seem to be of cardinal importance in shaping adolescents’ perception of safety practices in driving (e.g., wearing seatbelts when driving) [ 30 ], but it is also important in promoting self-regulation in emotions, protecting adolescents from engaging in risky behaviors [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation